2020
DOI: 10.3390/ijms21114158
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Mesothelial-Mesenchymal Transition in Chronic Peritoneal Diseases by Estrogen Receptor Modulation and TGF-β1 Inhibition

Abstract: In chronic peritoneal diseases, mesothelial-mesenchymal transition is determined by cues from the extracellular environment rather than just the cellular genome. The transformation of peritoneal mesothelial cells and other host cells into myofibroblasts is mediated by cell membrane receptors, Transforming Growth Factor β1 (TGF-β1), Src and Hypoxia-inducible factor (HIF). This article provides a narrative review of the reprogramming of mesothelial mesenchymal transition in chronic peritoneal diseases, drawing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 176 publications
2
34
0
Order By: Relevance
“…cn/ web/ GSCAL ite/). For each CRC patient, the tumor mutation burden (TMB) score is measured as follows: (total mutations/total covered bases) × 10 6 .…”
Section: Gene Mutation and Methylation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…cn/ web/ GSCAL ite/). For each CRC patient, the tumor mutation burden (TMB) score is measured as follows: (total mutations/total covered bases) × 10 6 .…”
Section: Gene Mutation and Methylation Analysismentioning
confidence: 99%
“…EMT can affect the occurrence and development of CRC, the prognosis of metastasis, and the effect of chemotherapy and immunotherapy [ 6 ]. However, the current research still lacks systematic research on the overall genes that regulate the EMT process and its prognosis and treatment effects with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…First, the PF model using CG may be a very strong fibrosis model, which did not fully prevent injuries byCG, despite SB treatment. Second, PF by intraperitoneally injected CG can be developed through other pathways, such as NF-κB via advanced glycation end products, or IL-1β, or ERK 1/2 via IL-6, or angiotensin, beyond TGF-β and its signaling pathways [29][30][31]. SB525334 can attenuate TGF-β and its downstream pathways, but may not completely prevent changes through other pathways than TGF-β and its signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Transitioned cells take on a motile phenotype and display an increase in mesenchymal cytoskeletal markers eventually becoming invasive and fully transitioned into alpha-smooth muscle actin (αSMA)- positive myofibroblasts [ 55 ]. The role of TGF-β1 in promoting MMT is well-documented [ 56 , 57 , 58 ] and several key signalling pathways associated with TGF-β, IL-1β, angiotensin II, HIF-1α, and pleiotrophin have been implicated [ 59 , 60 , 61 , 62 , 63 ]. By inducible genetic fate mapping, Chen and colleagues reported that sodium hypochlorite injured serosa is repaired by mesothelial cells positive for Wilms’ tumour protein 1 (WT1); however, they questioned the role of MMT in mediating peritoneal fibrosis [ 64 ].…”
Section: Serosal Repair and Adhesion Formationmentioning
confidence: 99%